Development of a Junior High School/Islamic Junior High School Science Module Integrating Islamic Values into the Human Coordination, Reproduction, and Homeostasis System Material - Dian Puspita; Nesvira Amanda; Rian Vebrianto; Susilawati Susilawati (ISEJ : Indonesian Science Education Journal, 2026)
Integrating religious meaning with disciplinary science requires teaching materials that preserve scientific explanations while making value connections explicit and pedagogically defensible. This study developed and evaluated an Islamic values-integrated science module on human coordination, reproductive, and homeostatic systems for Grade IX junior secondary students. Educational design research followed three Plomp phases: preliminary research, prototyping, and assessment. Preliminary research included interviews with two science teachers from UPT SMP Negeri 1 and SMP Negeri 4 in Kampar and a needs-analysis questionnaire completed by 31 Grade IX students. During prototyping, the module was reviewed across content, Islamic-integration, and media domains, with two expert ratings recorded for each domain. Limited assessment at UPT SMP Negeri 1 involved one science teacher for practicality appraisal and 31 students for user-response evaluation. Data were summarized using a five-point scale and percentage scores. The needs analysis showed strong demand for an integrated module: 90.32% of students supported its use, while 74.19% had never learned with a module integrating Islamic values on these human-system topics. Expert scores were 80.00% for content validity, 70.00% for Islamic-value integration, and 81.18% for media validity. Recalculation from the item-level practicality scores yielded 75.71% (practical), while student responses reached 86.65% (very positive). The integration domain was the weakest component, indicating a need for deeper conceptual alignment between Qur’anic or hadith references and biological explanations. The module is therefore best regarded as a feasible and practical supplementary/enrichment resource with strong student acceptability; its effectiveness for improving learning outcomes was not tested.